Pediatric endoscopic endonasal skull base surgery - Singh, Haminder; Greenfield, Jeffrey P.; Anand, Vijay K., 1951-; Schwartz, Theodore H. (Thieme, 2019)
"Today, expanded endonasal approaches (EEA) have revolutionized the surgical treatment paradigm for pediatric central skull base lesions. Specially adapted micro-instruments have been developed to permit passage through the narrow sinonasal pathways in children, enabling access to the entire midline skull base, from the crista galli to the cervico-medullary junction. Pediatric Endoscopic Endonasal Skull Base Surgery is the first textbook focused solely on endoscopic endonasal management of cranial base pathologies in children. The book reflects in-depth expertise from an extraordinary group of international contributors from five continents, who share extensive knowledge on this emerging field. Thirty four chapters are presented in three comprehensive sections. Key Features: 1) Core topics including anatomy, rhinological and anesthetic considerations, patient positioning and OR set-up, instrumentation, and endonasal corridors and approaches; 2) Fifteen chapters detail endoscopic treatment of a full spectrum of pediatric pathologies, such as encephalocele/meningoencephalocele, cysts, and benign and malignant tumors; 3) Discussion of multiple skull closure techniques, managing complications, and neurosurgical and otolaryngological postoperative care; 4) Visually rich, the succinct text is enhanced with 500 high-quality surgical illustrations and intraoperative photographs, as well as procedural videos. This unique reference is essential reading for neurosurgical and otolaryngology residents and fellows, as well as veteran surgeons, nurse-practitioners, and physician-assistants who treat and care for pediatric patients with skull-base conditions"--